Turning Pages Intelligently: AI Pop-Up Book as an Innovative Medium to Enhance English Reading Comprehension Among Elementary EFL Students - Evi Puspita Sari; Semi Sukarni; Ismawati Ike Nugraeni (Universitas Islam Negeri Palopo, 2026)
Can an AI-powered pop-up book genuinely move the needle on reading comprehension for young EFL learners? This study examined that question through a pre-experimental one-group pretest-posttest design involving 21 fifth-grade students at SD Negeri Sidomulyo, Indonesia. The AI Pop-Up Book media — combining interactive three-dimensional visuals with adaptive AI feedback — was implemented across structured reading sessions, with learning outcomes measured via a 15-item comprehension test and analyzed using Paired Samples t-Test and Normalized Gain (N-Gain). Results revealed a statistically significant improvement from a mean pretest score of 68.33 to a posttest score of 76.43 (t(20) = 3.179, p = 0.005), with a concurrent reduction in score variability suggesting more equitable learning gains across the class. While the group mean N-Gain of 0.072 appears modest, it is substantially skewed by a single ceiling-effect outlier; when excluded, over half the students (52.38%) achieved moderate to high individual gains. These findings demonstrate that AI Pop-Up Book media holds genuine promise for elementary EFL reading instruction, provided it is supported by adequate teacher scaffolding, digital literacy preparation, and extended implementation time.